Exergy analysis of a novel multi-stage latent heat storage device based on uniformity of temperature differences fields. (15th April 2021) - Li, Jiaqi; Tu, Rang; Liu, Mengdan; Wang, Siqi
Abstract: For shell-and-tube type latent heat storage devices, heat transfer rate reduces with time due to the increasement of ineffective heat transfer area. To solve this problem, a latent heat storage device, which is made of 'replaceable multi-stage' phase change plates (PCPs), is proposed in this paper. When one PCP has no heating ability, it is replaced by a new PCP. Effects of the 'replaceable multi-stage' configuration are evaluated using unmatched coefficient, which indicates uniformity of temperature differences distribution, and exergy destruction, which is influenced by the unmatched coefficient. Two replacement methods are numerically studied and based on the recommended method, effects of stage number and length of the device on heat transfer performances are investigated. It is found that, with length of the device being fixed, larger stage number results in smaller unmatched coefficient and lower exergy destruction. Therefore, higher and more stable supply air temperature can be realized. However, more frequent replacement actions are required if stage number is increased. For space heating applications, a 2-stage heating unit with length of each plate being 30 cm is recommended, which can heat indoor air from 20 °C to 29.5 °C for 8 h. Highlights: A novel device with 'replaceable multi-stage' phase change plates (PCP) is proposed. Ineffective PCP is replaced with a new PCP and two replacement methods are compared. The optimal method creates lower unmatched coefficient and higher exergy efficiency. Larger stage number leads to more stable outlet temperature of the working fluid. A 2-stage device that is 60 cm long is preferred for space heating applications.